2017
DOI: 10.1136/archdischild-2016-312208
|View full text |Cite
|
Sign up to set email alerts
|

Newborn infants with bilious vomiting: a national audit of neonatal transport services

Abstract: Objective: The precautionary approach to urgently investigate infants with bilious vomiting has increased the numbers referred to transport teams and tertiary surgical centres. The aim of this national UK audit was to quantify referrals, determine the frequency of surgical diagnoses, with the purpose to inform the consequent inclusion of these referals in the national 'time critical' dataset. Method:A prospective, multi-centre UK-wide audit was conducted (01 August 2015 to 31 October 2015). Term infants, ≤ 7 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 7 publications
(9 reference statements)
2
10
0
Order By: Relevance
“…Birthweight was not investigated as a factor in other studies; this study found a time‐critical diagnosis did decrease significantly with every increase in kilogram of weight (OR 0.48; 95% CI 0.29–0.77; P = 0.0024). The median weight of our cohort was similar to the other studies 4–6,10,11 . The clinical significance of this finding is unclear.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Birthweight was not investigated as a factor in other studies; this study found a time‐critical diagnosis did decrease significantly with every increase in kilogram of weight (OR 0.48; 95% CI 0.29–0.77; P = 0.0024). The median weight of our cohort was similar to the other studies 4–6,10,11 . The clinical significance of this finding is unclear.…”
Section: Discussionsupporting
confidence: 82%
“…The median weight of our cohort was similar to the other studies. [4][5][6]10,11 The clinical significance of this finding is unclear.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This may explain the higher incidence of surgical pathology demonstrated in these studies. [3][4][5][6]8]. Our study was population-based from a single centre from a cohort of 'well / normal' term infants, therefore unlikely to have a high incidence of underlying pathology.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that 15% of term infants less than 7 days old transferred by the London Neonatal Transport Service were for BV. [8]. An upper gastrointestinal contrast study (UGI) remains the best available radiological investigation for diagnosing malrotation with a positive predictive value of 90% [2], although ultrasonography has also been shown to be safe and reliable.…”
Section: Introductionmentioning
confidence: 99%